HUBUNGAN KADAR DEBU TOTAL DAN MASA KERJA DENGAN GANGGUAN FUNGSI PARU PADA PEDAGANG KAKI LIMA DI JALAN BRIGJEN SUDIARTO KOTA SEMARANG - Choirul Luluk Fatimah; Yusniar Hanani Darundiati; Tri Joko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Respiratory illness is the third most common cause of mortality in the world, following heart problems and cancer. In 2016 as many as 5.5 million people died each year due to respiratory problems exposed to air pollution. One of the groups at risk of air pollution is street vendors in Brigjend Sudiarto Street, Semarang City which has high dust content. The purpose of this study know the prevalence of lung fuction disorders as well as the relationship between the dust exposure (TSP), working period, and duration of exposure. The research of the street vendors in Brigjen Sudiarto Street, Semarang City as many as 40 people. The results of this study showed that 24 respondents have lung fuction disorders (60%). The results of statistical analysis showed between total dust content with pulmonary function disorder with p value of 0,020 (p <0,05). Prevalent Ratio Value (RP) = 2,280; 95% CI (1,078-4,821), and between working period and pulmonary function impairment with p value of 0,018 (p <0,05). Prevalent Ratio Value (RP) = 3,194; 95% CI (0.922-11,067). The conclusion of this research is the relation of total exposure to dust and working period on street vendors with lung function disorders in Brigjen Sudiarto Street Semarang City.